Reduced Dose Intensity of Daunorubicin During Remission Induction for Low-Risk Patients With Acute Lymphoblastic Leukemia: A Retrospective Cohort Study of the Chinese Children’s Cancer Group - Zhuang, Yong; Wu, Kefei; Zhu, Xiaofan; Cai, Jiaoyang; Hu, Shaoyan; Gao, Ju; Jiang, Hua; Zhai, Xiaowen; Tian, Xin; Fang, Yongjun; Jin, Runming; Hu, Qun; et al. (Frontiers in Oncology, 2022)
It is urgently necessary to reduce the adverse effects of chemotherapy while maintaining their cure high rates for children with acute lymphoblastic leukemia (ALL). The present study aimed to determine whether the dose intensity of daunorubicin during the remission-induction phase could be reduced for low-risk patients with ALL. A total of 2396 eligible patients, who participated in CCCG-ALL-2015 study and were provisionally assigned to the low-risk group, were included and divided into single-dose group and double-dose group according to the dosage of daunorubicin during the remission-induction phase. For patients with ETV6-RUNX1 positive ALL or hyperdiploidy ALL, there were no significant differences in outcomes between the two groups. For other patients, the 5-year event-free survival rate was significantly better and the 5-year cumulative risk of any relapse was significantly lower in the double-dose group compared with the single-dose group. Both the 5-year overall survival rate and the risk of early deaths were not significantly different between the two groups. Our results suggested that only B-lineage ALL patients with ETV6-RUNX1 positivity or hyperdiploidy who achieved an early negative minimal residual disease status were suitable candidates for dosage reduction of daunorubicin during the remission-induction phase.